SARS-CoV-2 sero-immunity and quality of life in children and adolescents in relation to infections and vaccinations: the IMMUNEBRIDGE KIDS cross-sectional study, 2022 - Engels, Geraldine; Oechsle, Anna-Lisa; Schlegtendal, Anne; Petersmann, Astrid; Schroten, Horst (Infection, 2023)
The study evaluates the effects on sero-immunity, health status and quality of life of children and adolescents after the upsurge of the Omicron variant in Germany.
Online veröffentlicht: 6. Juni 2023
Gesehen am 08.08.2024